Contouring consensus guidelines in breast cancer radiotherapy: Comparison and systematic review of patterns of failure. Issue 1 (29th September 2018) - Gee, Harriet E; Moses, Lauren; Stuart, Kirsty; Nahar, Najmun; Tiver, Ken; Wang, Tim; Ward, Rachel; Ahern, Verity
Summary: Adequate coverage of sites harbouring potential microscopic disease is paramount, where the clinical decision has been made to include regional lymph node radiotherapy for patients with breast cancer. This must be achieved in balance with minimising dose to normal tissues. Several international consensus guidelines detailing clinical target volumes (CTVs) are available, but there is currently no agreement as to which is most appropriate for a given clinical situation. Contouring guidelines are beneficial for routine practice and essential for clinical trial quality assurance. The aims of this study were as follows: to provide a single point of comparison of four commonly used contouring guidelines, including one used in a current Trans‐Tasman Radiation Oncology Group trial; and to undertake a systematic review of existing studies which map sites of breast cancer recurrence against contouring guidelines. Two international consensus guidelines (European Society for Radiotherapy and Oncology, and Radiation Therapy Oncology Group) were compared with two clinical trial guidelines (TROG 12.02 PET LABRADOR and the Proton/Photon trial NCT02603341 RADCOMP). Comprehensive literature search for patterns of failure studies was undertaken using Embase and Pubmed. We detail the small but significant differences between the breast consensus guidelines, particularly the supraclavicular (SCF) and internal mammary chain CTVs. Seven series were found mapping recurrence patterns. These results are discussed in the context of the contouring guidelines. Several studies found the SCF CTV is the area at greatest risk of geographical 'miss'. This review will facilitate further discussion about guideline selection and modification, particularly for future clinical trials in Australia and New Zealand.